Guidelines for adapting cognitive stimulation therapy to other cultures - Aguirre E (Dove Medical Press, 2014)
Elisa Aguirre,1,2 Aimee Spector,3 Martin Orrell1,2 1Division of Psychiatry, University College London, London, UK; 2Research and Development Department, North East London Foundation Trust, Goodmayes Hospital, Essex, UK; 3Clinical, Educational and Health Research Psychology Department, University College London, London, UK Abstract: Cognitive stimulation therapy (CST) has been shown to be an useful and cost effective intervention that increases cognition and quality of life of people with mild to moderate dementia. It is increasing in popularity in the UK and worldwide, and a number of research teams have examined its effectiveness in other contexts and cultures. However, it is necessary to develop clear evidence-based guidelines for cultural modification of the intervention. This article describes a community-based developmental approach to adapt CST to different cultures, following the five phases of the formative method for adapting psychotherapy (FMAP), an approach that involves collaborating with service users as a first step to generate and support ideas for therapy adaptation. Examples based on clinical and practical experience are presented, along with suggestions for applying these changes in different cultural contexts. Keywords: CST, culture, adaptation, mild to moderate dementia, dementia, FMAP